2x-4(x+1)=-2(x+2)

Simple and best practice solution for 2x-4(x+1)=-2(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-4(x+1)=-2(x+2) equation:


Simplifying
2x + -4(x + 1) = -2(x + 2)

Reorder the terms:
2x + -4(1 + x) = -2(x + 2)
2x + (1 * -4 + x * -4) = -2(x + 2)
2x + (-4 + -4x) = -2(x + 2)

Reorder the terms:
-4 + 2x + -4x = -2(x + 2)

Combine like terms: 2x + -4x = -2x
-4 + -2x = -2(x + 2)

Reorder the terms:
-4 + -2x = -2(2 + x)
-4 + -2x = (2 * -2 + x * -2)
-4 + -2x = (-4 + -2x)

Add '4' to each side of the equation.
-4 + 4 + -2x = -4 + 4 + -2x

Combine like terms: -4 + 4 = 0
0 + -2x = -4 + 4 + -2x
-2x = -4 + 4 + -2x

Combine like terms: -4 + 4 = 0
-2x = 0 + -2x
-2x = -2x

Add '2x' to each side of the equation.
-2x + 2x = -2x + 2x

Combine like terms: -2x + 2x = 0
0 = -2x + 2x

Combine like terms: -2x + 2x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 18k=-216 | | 0=0.2x^2-1.3x+3 | | 0.5*x-sin(x)=0 | | -5+2x-3x=-13 | | 5x+32=5x+9 | | 0.5*(x)-sin(x)=0 | | y^2+4x^2-32x=4y-64 | | 4x+3(4x-5)=-127 | | [5*(5a-5)-120]*5-25=125 | | sin(x)-0.5*(x)=0 | | (4m-18)=12 | | 1.86g-4=0.65 | | 2a-8+-1a=-4 | | (5b+11)=19 | | -108=3(4n-4) | | 9x^2+49y^2=392y-343 | | 2(x^2-2x+8)+3x^2-5x-9= | | -112=8(-6+8x) | | y=15x+75 | | 2x=10x+-40 | | 8x-x(x-5)=x+25 | | 23=5+2n-8n | | 3x+10=2(4x+50) | | 16=4m+4 | | -7y=14x | | -9=-4x-5x | | 8+3x=2x | | -8x+20y+4x^2=7-4y^2 | | 0=x^2+22x+112 | | 4(g+2)=2(4-g) | | -9=-x-5x | | c=8*3.14ab |

Equations solver categories